Association of empagliflozin treatment with albuminuria levels in patients with heart failure: a secondary analysis of EMPEROR-Pooled : original investigation - Pedro Ferreira, João; Zannad, Faiez; Butler, Javed; Filippatos, Gerasimos; Pocock, Stuart J.; Brückmann, Martina; Steubl, Dominik; Schueler, Elke; Anker, Stefan D.; Packer, Milton (JAMA cardiology, 2022)
Albuminuria, routinely assessed as spot urine albumin-to-creatinine ratio (UACR), indicates structural damage of the glomerular filtration barrier and is associated with poor kidney and cardiovascular outcomes. Sodium-glucose cotransporter-2 (SGLT2) inhibitors have been found to reduce UACR in patients with type 2 diabetes, but its use in patients with heart failure (HF) is less well studied.To analyze the association of empagliflozin with study outcomes across baseline levels of albuminuria and change in albuminuria in patients with HF across a wide range of ejection fraction levels.This post hoc analysis included all patients with HF from the EMPEROR-Pooled analysis using combined individual patient data from the international multicenter randomized double-blind parallel-group, placebo-controlled EMPEROR-Reduced and EMPEROR-Preserved trials. Participants in the original trials were excluded from this analysis if they were missing baseline UACR data. EMPEROR-Preserved was conducted from March 27, 2017, to April 26, 2021, and EMPEROR-Reduced was conducted from April 6, 2017, to May 28, 2020. Data were analyzed from January to June 2022.Randomization to empagliflozin or placebo.New-onset macroalbuminuria and regression to normoalbuminuria and microalbuminuria.A total of 9673 patients were included (mean [SD] age, 69.9 [10.4] years; 3551 [36.7%] female and 6122 [63.3%] male). Of these, 5552 patients had normoalbuminuria (UACR <30 mg/g) and 1025 had macroalbuminuria (UACR >300 mg/g). Compared with normoalbuminuria, macroalbuminuria was associated with younger age, races other than White, obesity, male sex, site region other than Europe, higher levels of N-terminal pro-hormone brain natriuretic peptide and high-sensitivity troponin T, higher blood pressure, higher New York Heart Association class, greater HF duration, more frequent previous HF hospitalizations, diabetes, hypertension, lower eGFR, and less frequent use of angiotensin-converting enzyme inhibitors or angiotensin receptor blockers and mineralocorticoid receptor antagonists. An increase in events was observed in individuals with higher UACR levels. The association of empagliflozin with cardiovascular mortality or HF hospitalization was consistent across UACR categories (hazard ratio [HR], 0.80; 95% CI, 0.69-0.92 for normoalbuminuria; HR, 0.74; 95% CI, 0.63-0.86 for microalbuminuria; HR, 0.78; 95% CI, 0.63-0.98 for macroalbuminuria; interaction P trend = .71). Treatment with empagliflozin was associated with lower incidence of new macroalbuminuria (HR, 0.81; 95% CI, 0.70-0.94; P = .005) and an increase in rate of remission to sustained normoalbuminuria or microalbuminuria (HR, 1.31; 95% CI, 1.07-1.59; P = .009) but not with a reduction in UACR in the overall population; however, UACR was reduced in patients with diabetes, who had higher UACR levels than patients without diabetes (geometric mean for diabetes at baseline, 0.91; 95% CI, 0.85-0.98 and for no diabetes at baseline, 1.08; 95% CI, 1.01-1.16; interaction P = .008).In this post hoc analysis of a randomized clinical trial, compared with placebo, empagliflozin was associated with reduced HF hospitalizations or cardiovascular death irrespective of albuminuria levels at baseline, reduced progression to macroalbuminuria, and reversion of macroalbuminuria.ClinicalTrials.gov Identifiers: NCT03057977 and NCT03057951
Gesehen am 18.06.2024